Reactive Direct Bonding of Digital Light Process Components - Moritzer, Elmar; Driediger, Christine (Macromolecular Symposia)
Keywords: digital light processing; material combination; reactive direct bonding; vat photopolymerization

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric generalized autoregressive conditional heteroscedasticity (GARCH) models with long memory are introduced. A multiplicative decomposition of the volatility into a conditional component and an unconditional component is assumed. The estimation of the latter is carried out by means of a data-driven local polynomial smoother. According to the revised recommendations by the Basel Committee on Banking Supervision to measure market risk in the banks’ trading books, these new semiparametric GARCH models are applied to obtain rolling one-step ahead forecasts for the value-at-risk and expected shortfall (ES) for market risk assets. Standard regulatory traffic-light tests and a newly introduced traffic-light test for the ES are carried out for all models. In addition, model performance is assessed via a recently introduced model selection criterion. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long-memory GARCH models are a meaningful substitute for their conventional, parametric counterparts.
Keywords: long memory; generalized autoregressive conditional heteroscedasticity (GARCH) models; value-at-risk (VaR); expected shortfall (ES); traffic-light test; backtesting

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric GARCH models with long memory are in- troduced. The estimation of the nonparametric scale function is carried out by an adapted version of the SEMIFAR algorithm (Beran et al., 2002). Recurring on the revised recommendations by the Basel Committee to measure market risk in the banks' trading books (Basel Committee on Banking Supervision, 2013), the semi- parametric GARCH models are applied to obtain rolling one-step ahead forecasts for the Value at Risk (VaR) and Expected Shortfall (ES) for market risk assets. In addition, standard regulatory traffic light tests (Basel Committee on Banking Supervision, 1996) and a newly introduced traffic light test for the ES are carried out for all models. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long memory GARCH models are an attractive alternative to their conventional, parametric counterparts.
Keywords: Semiparametric; long memory; GARCH models; forecasting; Value at Risk; Expected Shortfall; traffic light test; Basel Committee on Banking Supervision

Nonlinear waveguides for integrated quantum light source - Domeneguetti, Renato R.; Conradi, Hauke; Kleinert, Moritz; Kießler, Christian; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas Schou; Gehring, Tobias (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference)
We experimentally investigate the generation of continuous-wave optical squeezing from a titanium-indiffused lithium niobate waveguide resonator at low and high frequencies. The device promises integration with different platform chips for more complex optical systems.
Keywords: Optical systems; Polymer waveguides; Quantum key distribution; Quantum light sources; Squeezed states; Waveguides

Optimising Tours for the Weighted Traveling Salesperson Problem and the Traveling Thief Problem: A Structural Comparison of Solutions - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Parallel Problem Solving from Nature (PPSN XVI))
The Traveling Salesperson Problem (TSP) is one of the best-known combinatorial optimisation problems. However, many real-world problems are composed of several interacting components. The Traveling Thief Problem (TTP) addresses such interactions by combining two combinatorial optimisation problems, namely the TSP and the Knapsack Problem (KP). Recently, a new problem called the node weight dependent Traveling Salesperson Problem (W-TSP) has been introduced where nodes have weights that influence the cost of the tour. In this paper, we compare W-TSP and TTP. We investigate the structure of the optimised tours for W-TSP and TTP and the impact of using each others fitness function. Our experimental results suggest (1) that the W-TSP often can be solved better using the TTP fitness function and (2) final W-TSP and TTP solutions show different distributions when compared with optimal TSP or weighted greedy solutions.
Keywords: Evolutionary algorithms; Node weight dependent TSP; Traveling Thief Problem

In vitro evaluation of innovative light-responsive nanoparticles for controlled drug release in intestinal PDT - Mahlert, Laura; Anderski, Juliane; Schoppa, Timo; Mulac, Dennis; Sun, Jingjiang; Kuckling, Dirk; Langer, Klaus (International Journal of Pharmaceutics)
Keywords: Light-responsive polymersPhotodynamic therapyControlled drug deliveryHT-29-MTX cellsIntestinal cancer

Light-Responsive Serinol-Based Polycarbonate and Polyester as Degradable Scaffolds - Sun, Jingjiang; Jung, Dimitri; Schoppa, Timo; Anderski, Juliane; Picker, Marie-Theres; Ren, Yi; Mulac, Dennis; Stein, Nora; Langer, Klaus; Kuckling, Dirk (ACS Applied Bio Materials)
Keywords: light-responsive polymers; biodegradable polymers; polycondensation

Spring forward, don’t fall back: The effect of daylight saving time on road safety - Bünnings, Christian; Schiele, Valentin
Keywords: road accidents; light conditions; daylight saving time

Server-based execution of periodic tasks on dynamically reconfigurable hardware - Danne, Klaus; Mühlenbernd, Roland; Platzner, Marco (IET Computers Digital Techniques)
Keywords: reconfigurable architectures; resource allocation; device reconfiguration time; dynamic hardware reconfiguration; dynamically reconfigurable hardware; light-weight runtime system; merge server distribute load; periodic real-time tasks; runtime system overheads; schedulability analysis; scheduling technique; server-based execution; synthesis tool flow

Credible Threats as an Instrument of Regulation for Network Industries - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (REGULATORY CHANGES, INNOVATIONS AND INVESTMENT DYNAMICS IN THE DIGITAL WORLD ECONOMY)
In order to avoid over-regulation, some countries have experimented with what might be called threat-based regulation. The idea is - similarly to the contestable market model - that actual regulation may not be necessary as long as the threat of regulation is credible. In that case, so the idea, even monopolies will abstain from setting monopolistic prices in order to avoid being regulated. As experience from Germany and New Zealand has demonstrated, there are quite a number of problems associated with threat-based regulatory systems. The most significant problem has turned out to be the likely under-regulation and according welfare losses from market power, and in this context, a critical issue that has been identified is the credibility of the regulatory threat. If the threat of regulation is not credible, a light-handed regulatory regime (LHRR) amounts to leaving monopolistic firms unregulated, clearly an undesirable situation from a welfare point of view. This failure of threat-based regulatory systems results from potential free-rider problems associated with good corporate behaviour (as in the case of Germany's electricity market) as well as the lack of credibility of the threat either because of the weakness of the enforcement authorities or due to political constraints. Furthermore, a problem emerges if exercising the threat of regulation implies an abandonment of the LHRR and a corresponding substitution with heavy-handed ex ante regulation. An innovative way out of this dilemma has been the quasi-automatic threshold system originally designed for New Zealand's electricity distribution networks, which aims at simulating the pressures that companies would face in competitive markets.
Keywords: light-handed regulation; network industries; electricity; telecommunications

Piezoelectric transformers - state of the art and development trends - Hemsel, Tobias; Littmann, Walter; Wallaschek, Jörg (Ultrasonics Symposium, 2002. Proceedings. 2002 IEEE)
Piezoelectric transformers are well known since the publication of some patent applications at the end of the 1950s. But until today their only business use lies in the field of backlighting systems for LCDs. Due to key features as light-weight, flatness, high step-up at low volume and high efficiency piezoelectric transformers should be usable in a much broader range of applications. This contribution returns to mind their operating principle, shows how to model and to develop such devices as well as give some aspects for development trends that will lead to further applications.
Keywords: piezoelectric devices; reviews; transformers; backlighting systems; flatness; high efficiency piezoelectric transformers; high step-up; light-weight; low volume; operating principle; piezoelectric transformers; Circuits; Costs; Electromagnetic devices; Electromagnetic fields; Mechanical energy; Piezoelectric materials; Power electronics; Switching frequency; Transformers; Vibrations